Improving Elementary School Students’ Learning Outcomes in Islamic Cultural History through Problem-Based Learning - Elda Malasari; Sukarno Sukarno (Jurnal Indonesia Pendidikan Profesi Guru, 2026)
Background: Low student learning outcomes in the subject of Islamic Cultural History (SKI) are caused by the use of monotonous teaching methods that do not actively engage students in the learning process. Objective: This study aimed to improve students’ learning outcomes by implementing the Problem-Based Learning (PBL) method in the SKI subject on the topic of the Prophet Muhammad’s migration and the establishment of Medina for fourth-grade students at SD Negeri 46 Bengkulu Tengah. Method: This study employed Classroom Action Research (CAR) across two cycles, involving 22 students. Data were collected through tests and observations, and data analysis used mastery learning percentages. Results: The findings revealed that implementing the PBL method significantly improved students’ learning outcomes. In Cycle I, the learning mastery percentage reached 27% with an average score of 64, while in Cycle II it increased to 86% with an average score of 75.5. Students also became more active and engaged during the learning process through problem-solving activities and group discussions. Conclusion: The study concludes that the Problem-Based Learning method is effective in improving students’ learning outcomes in the SKI subject. Contribution: This research provides an innovative instructional strategy to enhance student engagement, critical thinking, and understanding in Islamic Cultural History learning at the elementary school level.